Performance-Based Rewards, Disciplinary Sanctions, and Operator Performance in the Mining Industry - Muhammad Ichsan Hadjri; Afriyadi Cahyadi; arieffauzan (Jurnal Ragam Pengabdian, 2026)
Operator performance plays a critical role in supporting productivity and occupational safety in the mining industry, which is characterized by high operational risks. However, variations in operator performance remain a managerial challenge, particularly regarding the effectiveness of reward and punishment systems. This study aims to examine the effects of rewards and punishments on operator performance in a mining service company. The Research employed a quantitative, causal Research design. Data were collected through a structured questionnaire distributed to 150 heavy equipment operators, selected purposively from a total population of 370. The data were analyzed using multiple linear regression analysis to assess both partial and simultaneous effects of reward and punishment on operator performance. The findings indicate that rewards have a positive and significant Influence on operator performance, suggesting that fair, performance-based reward systems enhance motivation and work effectiveness. Punishment also shows a positive and significant effect, indicating that proportional and consistent sanctions contribute to improved work discipline and compliance with operational procedures. Furthermore, reward and punishment jointly explain a substantial proportion of the variation in operator performance. These results highlight the importance of balancing motivational incentives and behavioral control mechanisms in human resource management practices. The study concludes that well-designed reward and punishment systems are essential for achieving sustainable improvements in operator performance, particularly in high-risk industrial environments such as mining operations.